2001
DOI: 10.1677/jme.0.0270175
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor gene expression in rat mammary gland: structural characterization and regulation

Abstract: The differential, tissue-specific regulation of oxytocin (OT) binding sites allows the neurohypophysial nonapeptide OT to fulfill a dual role: to induce uterine contractions at parturition and to mediate milk ejection during lactation. Whereas uterine OT binding sites are up-regulated prior to parturition and are rapidly down-regulated thereafter, mammary gland OT binding sites gradually increase throughout gestation and remain up-regulated during the ensuing lactation period. Here, we structurally characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 48 publications
2
21
0
1
Order By: Relevance
“…On the other hand, oestrogen administration to castrated rat up-regulated OTR mRNA expression in the uterus whereas it did not affect its expression in the mammary gland. Even in the identical endocrine circumstance in vivo, the regulation of the OTR gene is different depending on the tissue (Breton et al 2001). In the human OTR gene, we could not find such a palindromic ERE in the area comparable to that of the rat gene (Y Mizumoto & T Kimura, unpublished observations).…”
Section: The Otr Gene and Its Transcriptional Regulationmentioning
confidence: 91%
“…On the other hand, oestrogen administration to castrated rat up-regulated OTR mRNA expression in the uterus whereas it did not affect its expression in the mammary gland. Even in the identical endocrine circumstance in vivo, the regulation of the OTR gene is different depending on the tissue (Breton et al 2001). In the human OTR gene, we could not find such a palindromic ERE in the area comparable to that of the rat gene (Y Mizumoto & T Kimura, unpublished observations).…”
Section: The Otr Gene and Its Transcriptional Regulationmentioning
confidence: 91%
“…The effect of P on OTR expression is controversial. It has been suggested that, through the nuclear receptors, P inhibits the OTR mRNA expression, and makes the target cell less sensitive to OT stimulation [25,26,[37][38][39][40][41][42][43] . Giacalone also reported that, RU-486, a P receptor antagonist, increases the incidences of tachysystole, hypertonia and fetal heart rat abnormality [44] .…”
Section: Liu Cy Et Al P and Gl Motility 339mentioning
confidence: 99%
“…Its primary function is to mediate the milk ejection reflex in nursing mammals (1). It also augments uterine contraction during parturition (2).…”
mentioning
confidence: 99%